Hubungan antara Motivasi Kemandirian Belajar dan Persepsi Siswa terhadap Matematika dengan Prestasi Belajar Siswa SMK - Ririn Sri Lestari; Agustina Sri Purnami; Tri Astuti Arigiyati (Universitas Sarjanawiyata Tamansiswa, 2021)
This research aims to determine the relation between motivation, learning independence and students’ perception of mathematics with the learning achievements of grade X of Vocational High School in Umbulharjo district both jointly and independently. The study was conducted at Vocational School in Umbulharjo district using the ex post facto method. A sample of 122 was taken by cluster random sampling. Data collection using questionnaire and test techniques. data analysis techniques used multiple linear regression analysis. The result of the study showed that there was a positive and significant relationship between motivation, learning independence and students’ perception of mathematics with students’ achievement both jointly and independently. This can be seen from the sig value of each motivational variable by 0.005 < 0.05, learning independence by 0.000 < 0.05 and students’ perception of mathematics by 0.002 < 0.05.